The Influence of Product Quality, Live Streaming, and Online Reviews in the TikTok Application on Purchase Decisions (A Study on Ponds) - Shakira, Azura Maharani; Indrajaya, Sonny (Dinasti International Journal of Management Science, 2025)
This study aims to analyze the impact of product quality, live streaming, and online reviews on purchasing decisions on Ponds in the TikTok Application. This research is quantitative research. The population in this research is uncertain. This research used a 140 sample with a purposive sampling for analyzed. The questionnaire presents statements that respondents must choose from strongly agree to strongly disagree on a Likert scale of 1-5 points. The analysis method was carried out using partial least square through the SmartPLS 4.0 statistical software. The results of the study show that quality product has a positive and significant effect on purchasing decisions, live streaming has a positive and significant effect on purchasing decisions, and online reviews have a positive and significant effect on purchasing decisions.